Expression of TASK-1 channel in mouse Leydig cells - Woo, Min Seok; Kim, Eun-Jin; Prayoga, Anjas Happy; Kim, Yangmi; Kang, Dawon (Journal of animal reproduction & biotechnology (Online), 2023)
Background: Leydig cells, crucial for testosterone production, express ion channels like ANO1 that influence hormone secretion. This study investigates the expression and role of the Tandem of P domains in a weak inward rectifying K+ channel-related Acid-Sensitive K+-1 (TASK-1) channel in these cells, exploring its impact on testicular function and steroidogenesis. Methods: TASK-1 expression in Leydig cells was confirmed using immunostaining, while RT-PCR and Western Blot (WB) validated its expression in the TM3 Leydig cell line. The effect of a TASK-1 channel blocker on cell viability was assessed through live/dead staining and MTT assays. Additionally, the blocker’s effect on testosterone secretion was evaluated by measuring testosterone levels. Results: Immunohistochemical analysis revealed a predominant presence of TASK- 1, along with c-Kit and ANO-1, in Leydig cells adjacent to seminiferous tubules and also in Sertoli and spermatogenic cells. Expression levels of TASK-1 mRNA and protein were significantly higher in TM3 Leydig cells compared to TM4 Sertoli cells. In addition, blocking TASK-1 in TM3 cells with ML365 induced cell death but did not affect LHinduced testosterone secretion. Conclusions: These findings suggest that TASK-1 in Leydig cells is crucial for their viability and proliferation, highlighting its potential importance in testicular physiology.